The Comparison between Explosive Cyclone and Typhoon over Northern Japan in the Current and Future Climate. (2016) - Kitano, Yoshikazu; Yamada, Tomohito J.
Abstract: In the middle of December 2014, a storm surge induced by explosive cyclone struck Nemuro, a city located in Hokkaido, Northern Japan, causing immense damage due to flooding. This explosive cyclone suddenly intensified along the east coast of Tohoku region and remained stationary near the Nemuro Bay due to the atmospheric blocking which existed over the Sea of Okhotsk. In this study, we analyze the moving velocity of explosive cyclones in 1960 to 1999 and they are compared with those of typhoons considered as another meteorological cause for storm surge. Furthermore, we discuss synoptic fields in which explosive cyclones move slowly in Northern Japan utilizing an atmospheric blocking diagnosis method.